일 치과의원의 구강건강관리 프로그램 효과와 재이용 의도 - 김정술(Jung-Sool Kim) (한국구강보건과학회지, 2018)
In this paper, we surveyed 120 subjects across numerous clinics from January to December, 2016, in order to analyze the realities and effects of preventive dental management programs. Based on the results of 98 sets of data, we concluded the following: First, the subjects want to regularly visit a clinic once a year. They also believe the aspect of tooth care which could be best improved after oral management is their method of brushing. They believe the best test is microscopic inspection, the best curing technique is T.B.I. and the reason most commonly given for infrequent visits to the clinic is expense. Additionally, a more appropriate visitation frequency would be once per month, whilst the appropriate healing time is 30 minutes or one hour. Second, the effects between pre- and post-management were statistically significant (P<.05); correlation analysis was also statistically significant (P<.05) with regard to preventive program satisfaction, care technique, and revisiting intentions. Third, regression analysis on revisiting intentions was also statistically significant (P<.05), with 37% expressing satisfaction with the preventive program and 9% with the curing technique. KCI Citation Count: 2